Effects of benzodiazepine on neuromuscular activity performance in archers - Ergen, E.; Açikada, C.; Hazir, T.; Güner, R.; Cilli, M.; Ergün Acar, Y. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of the study was to investigate the effects of benzodiazepine on shooting performance and its components in archers. In order to evaluate the possible effects of benzodiazepine, performance related parameters of body sway, mechanical clicker reaction time, aiming behavior and heart rate values were measured.